Method for preparing two-dimensional biomass carbon material by hydrodynamic cavitation assisted impregnation activator

The preparation of two-dimensional biomass carbon materials by hydraulic cavitation assisted impregnation of activator is solved, and the problems of complex preparation process, unfriendly environment and poor performance of carbon electrode materials in the prior art are achieved, and supercapacitor electrode materials with high specific capacitance and long discharge time are realized.

CN115775690BActive Publication Date: 2025-04-04SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211640732.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-04-04
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

The prior art has a series of problems such as long preparation process cycle, complex process, unfriendly to the environment, and poor performance when preparing carbon electrode materials for supercapacitors.

Method used

Two-dimensional biomass carbon materials are prepared by hydrocavitation assisted impregnation of activators. Through-holes and micropores are formed through hydrocavitation treatment, specific surface area is increased, and uniform micropores and mesopores are formed through activation heat treatment.

Benefits of technology

The specific surface area and micropore volume of two-dimensional biomass carbon materials have been significantly improved. The specific capacitance of supercapacitors prepared as electrode materials has been greatly improved, the discharge time is longer, and the process is economical and environmentally friendly, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115775690B_ABST
    Figure CN115775690B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of advanced material technology, relates to the preparation of electrode materials, and relates to a method for preparing two-dimensional biomass carbon materials by hydrodynamic cavitation-assisted impregnation with an activator. The method comprises the following steps: providing a biomass carbonized sample; adding the biomass carbonized sample and the activator to water and mixing them evenly, then subjecting the sample to hydrodynamic cavitation treatment, and then drying to obtain a dried sample; subjecting the dried sample to activation heat treatment to obtain an activated sample; and subjecting the activated sample to purification treatment to obtain the obtained sample. The method provided by the present invention is not only economical, environmentally friendly, simple and easy to implement, but also the obtained two-dimensional biomass carbon material has better performance as an electrode material for a supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of advanced materials, relates to the preparation of electrode materials, and relates to a method for preparing two-dimensional biomass carbon materials by hydrodynamic cavitation-assisted impregnation with an activating agent. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] The nanosheets formed by the exfoliation of two-dimensional layered materials can not only provide a unique nanoscale reaction space for electrochemical reactions, but also the layered nanoelectrode materials assembled from them have chemical and structural redox reversibility and fast ion or electron transmission channels in the horizontal direction of the nanosheets. At present, direct activation of carbon-rich materials such as wood blocks, nut shells, and coal blocks is the main technology for obtaining activated carbon materials, but there are a series of problems such as long preparation cycle, complex process, environmental unfriendliness, and poor performance. Summary of the invention

[0004] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing two-dimensional biomass carbon materials by hydrodynamic cavitation-assisted impregnation activator, which method is not only economical, environmentally friendly, simple and easy to implement, but also the obtained two-dimensional biomass carbon materials have better performance as electrode materials for supercapacitors.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In one aspect, a method for preparing a two-dimensional biomass carbon material by impregnation with an activator assisted by hydrodynamic cavitation comprises the following steps:

[0007] Provide biomass carbonization samples;

[0008] The biomass carbonized sample and the activator are added into water and mixed evenly, and then subjected to a hydrodynamic cavitation treatment, and then dried to obtain a dried sample;

[0009] The dried sample is subjected to activation heat treatment to obtain an activated sample;

[0010] The activated sample is purified.

[0011] On the other hand, a two-dimensional biomass carbon material is prepared by the above method.

[0012] In a third aspect, an application of the above two-dimensional biomass carbon material as an electrode material in a supercapacitor.

[0013] The beneficial effects of the present invention are:

[0014] In the present invention, when the same activator is impregnated, the hydrodynamic cavitation-assisted impregnation activator can greatly increase the specific surface area of ​​the biochar material, thereby achieving the purpose of biochar modification. The hydrodynamic cavitation technology can release huge energy instantly, which is manifested as a local hot spot up to 5000K; 1000bar high pressure, accompanied by powerful shock waves and high-speed microjets (150m / s). The impact force generated by the high-speed microjets can penetrate the biochar to form through holes; in addition, under the above extreme conditions, water molecules can be hydrolyzed, and the generated hydroxyl radicals, perhydroxyl radicals and strong oxidizing substances such as hydrogen peroxide react with carbon molecules; the local high temperature of 5000K can promote some water molecules to react with biochar, and at the same time promote the activator vapor to enter the internal microchannel structure of the activated carbon, and can further form micropores and mesopores of uniform size and uniform distribution through activation heat treatment, so that more active sites can be exposed and the specific surface area can be increased; the use of hydrodynamic cavitation technology can further remove impurities in the biomass porous carbon, thereby increasing the conductivity of the porous carbon material.

[0015] Experiments have shown that the specific surface area and micropore volume of the two-dimensional biomass carbon material prepared by hydrodynamic cavitation-assisted impregnation activator have increased. At the same time, the specific capacitance of the supercapacitor prepared as an electrode material has been significantly improved, which can be increased by 911.952% compared with the untreated sample.

[0016] The hydraulic cavitation treatment used in the present invention has the advantages of low cost, large processing volume, and easy scale-up. The method of preparing carbon materials by using hydraulic cavitation technology to assist in impregnation of activating agents can realize large-scale industrial production, save costs, increase output, and further improve economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 is a process flow chart of an embodiment of the present invention;

[0019] Figure 2 TEM photos of the two-dimensional structured carbon material obtained by hydrodynamic cavitation-assisted impregnation with an activator in Examples 1 and 2 of the present invention, (a) is Example 1, and (b) is Example 2;

[0020] Figure 3 The N2 desorption curves of the two-dimensional structured carbon materials prepared by hydrodynamic cavitation-assisted impregnation activator in the embodiments of the present invention and the comparative examples, (a) is the adsorption amount curve, and (b) is the differential volume curve;

[0021] Figure 4The XPS results of the two-dimensional structured carbon materials prepared by the hydrodynamic cavitation assisted impregnation activator of the embodiments of the present invention and the comparative examples, (a) is the XPS full spectrum scan, (b) is the C1s spectrum of the KOH (1:4) sample, (c) is the C1s spectrum of the KOH (1:4) + HC sample, (d) is the C1s spectrum of the KOH (1:8) sample, (e) is the C1s spectrum of the KOH (1:8) + HC sample, (f) is the O1s spectrum of the KOH (1:4) sample, (g) is the O1s spectrum of the KOH (1:4) + HC sample, (h) is the O1s spectrum of the KOH (1:8) sample, and (i) is the O1s spectrum of the KOH (1:8) + HC sample

[0022] Figure 5 The supercapacitor made of the two-dimensional carbon material prepared by hydrodynamic cavitation assisted impregnation activator in the embodiment of the present invention and the comparative example has a current density of 1A g -1 GCD curve when

[0023] Figure 6 This is a graph of the capacitance retention rate after 5000 charge and discharge cycles of a supercapacitor made of a two-dimensional structured carbon material prepared by hydrodynamic cavitation-assisted impregnation activator in the embodiments of the present invention and the comparative example. DETAILED DESCRIPTION

[0024] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0026] Hydrodynamic cavitation refers to the powerful shock waves and high-speed microjets formed by the collapse of cavitation bubbles, which can form strong disturbances and huge shear forces in the liquid, while impacting the surface of the object. The high temperature and high pressure environment formed by the collapse of cavitation bubbles, as well as the resulting polymer decomposition, chemical bond breaking and free radical generation.

[0027] In view of the fact that the existing carbon electrode materials for supercapacitors have a series of problems such as long preparation cycle, complex process, environmental unfriendliness and poor performance, the present invention proposes a method for preparing two-dimensional biomass carbon materials by hydrodynamic cavitation assisted impregnation activator.

[0028] A typical embodiment of the present invention provides a method for preparing a two-dimensional biomass carbon material by impregnation with an activator assisted by hydrodynamic cavitation, comprising the following steps:

[0029] Provide biomass carbonization samples;

[0030] The biomass carbonized sample and the activator are added into water and mixed evenly, and then subjected to a hydrodynamic cavitation treatment, and then dried to obtain a dried sample;

[0031] The dried sample is subjected to activation heat treatment to obtain an activated sample;

[0032] The activated sample is purified.

[0033] The present invention can not only form through holes in the biochar through hydraulic cavitation treatment, but also the formed local hot spots can prompt the activator vapor to enter the internal microchannel structure of the activated carbon. Through activation heat treatment, micropores and mesopores with uniform size and distribution can be further formed, so that more active sites can be exposed and the specific surface area can be increased.

[0034] Studies have shown that the two-dimensional biomass carbon material prepared by the method of the present invention not only has a higher specific surface area and micropore volume, but also the supercapacitor prepared as an electrode material has a more significant specific capacitance.

[0035] In some embodiments, the mass ratio of the biomass carbonized sample to the activator is 1:2 to 10. Studies have shown that when the mass ratio of the biomass carbonized sample to the activator is 1:7 to 9, the supercapacitor prepared from the two-dimensional biomass carbon material has a higher specific capacitance and a longer discharge time.

[0036] In some embodiments, the activating agent includes but is not limited to potassium hydroxide, sodium hydroxide, and hydrochloric acid.

[0037] In some embodiments, the hydrodynamic cavitation treatment uses a venturi-type hydrodynamic cavitation device, wherein the venturi-type hydrodynamic cavitation device has a pipe diameter of 10 to 30 mm, a throat diameter of 1 to 5 mm, and a contraction angle and an expansion angle between 10° and 50°.

[0038] In one or more embodiments, the hydrodynamic cavitation treatment conditions are: the venturi tube inlet pressure is 0.5-4 MPa, the treatment temperature is 30-70° C., and the treatment time is 10-120 min.

[0039] In some embodiments, the drying temperature after the hydrodynamic cavitation treatment is 100-200°C.

[0040] In some embodiments, the activation heat treatment is carried out under an inert atmosphere, and the process is: first heating to 50-400° C., keeping the temperature for 0.1-3 hours, and then continuing to heat to a set temperature of 600-900° C., keeping the temperature for 1-3 hours.

[0041] In some embodiments, the biomass carbonization sample is obtained by pyrolysis carbonization of biomass. The biomass includes but is not limited to garlic peels, sawdust, straw, rice husks, etc. In the present invention, garlic peel biomass material is used as an example, which has a better effect.

[0042] In one or more embodiments, the heating rate of pyrolysis carbonization is 1 to 10°C / min, and the holding time is 1 to 2 hours. Pyrolysis carbonization is generally carried out in an inert atmosphere (an atmosphere formed by nitrogen or an inert gas). When pyrolysis carbonization is carried out in a tubular furnace, the introduction of nitrogen or inert gas is stopped when the temperature of the tubular furnace drops to 50 to 300°C. The flow rate of nitrogen or inert gas is 0.5 to 3 L / h.

[0043] In some embodiments, the purification treatment includes water washing and acid treatment. Water washing refers to dispersing the activated sample in water to form a first turbid liquid, heating and stirring, standing to precipitate, removing the supernatant, repeating until the supernatant is neutral, and obtaining a final turbid liquid. Acid treatment refers to adding hydrochloric acid to the final turbid liquid, heating and stirring, standing, washing the precipitate to neutrality, and drying. The heating and stirring temperature is 60 to 100°C, and the heating and stirring time is 10 to 40 minutes. Add hydrochloric acid until the supernatant pH is 1 to 6. The drying time is 2 to 30 hours, and the drying temperature is 20 to 200°C.

[0044] The preferred preparation process of the present invention is as follows:

[0045] (1) placing garlic peel biomass material in a tubular resistance furnace; carbonizing under a nitrogen atmosphere, and obtaining a carbonized sample after naturally cooling to room temperature;

[0046] (2) mixing the carbonized sample obtained in step (1) with potassium hydroxide in a certain mass ratio, adding deionized water and stirring evenly; placing the obtained slurry mixture in a hydrodynamic cavitation treatment device for hydrodynamic cavitation treatment, and placing the treated sample in a blast drying oven for drying;

[0047] (3) adding a small amount of deionized water to the dried sample obtained in step (2), mixing evenly, and placing the mixture in a muffle furnace for activation to obtain an activated sample;

[0048] (4) dissolving the activated sample obtained in step (3) in deionized water to obtain a turbid solution; heating the obtained turbid solution in a water bath and subjecting it to magnetic stirring, and then allowing the sample to settle, discarding the supernatant, and repeating this step until the supernatant is neutral to obtain a turbid solution;

[0049] (5) Add an appropriate amount of hydrochloric acid to the turbid liquid obtained in step (4), heat it in a water bath and stir it magnetically, then let the turbid liquid stand, wash the precipitate with deionized water until it is neutral, and then dry it in a forced air drying oven to obtain activated carbon.

[0050] Another embodiment of the present invention provides a two-dimensional biomass carbon material prepared by the above method.

[0051] The specific surface area of ​​the two-dimensional structure biomass material prepared by the present invention is greater than 2720.904m 2 / g, which is 911.952% higher than that before treatment; when used as a supercapacitor electrode material, under constant current discharge of 5A / g, the specific capacity is greater than 300.004F / g, and there is no capacity decay after 5000 constant current charge and discharge at 5A / g.

[0052] A third embodiment of the present invention provides an application of the above two-dimensional biomass carbon material as an electrode material in a supercapacitor.

[0053] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0054] Comparative Example 1

[0055] Take garlic peel biomass material and place it in a tubular resistance furnace; heat it to the required carbonization temperature under a nitrogen atmosphere and keep it for 2 hours, with a heating rate of 5°C / min and a nitrogen flow rate of 1L / min; stop introducing nitrogen when the temperature of the tubular furnace drops to 100°C; after naturally cooling to room temperature, a carbonized sample is obtained, and sample 1 is obtained.

[0056] The prepared sample 1 was mixed evenly with conductive graphite and polytetrafluoroethylene solution (60wt%) in a mass ratio of 8:1:1 and a certain amount of anhydrous ethanol, and ultrasonically mixed for 30 minutes, and then coated on a nickel foam disc with a diameter of 1.5 cm. After vacuum drying at 80°C for 12 hours, the conductive electrode was obtained by pressing. The two electrodes, the glass fiber diaphragm and the battery shell were immersed in an electrolyte of 6M KOH, and the supercapacitor was assembled in the order of anode shell, conductive electrode, glass fiber diaphragm, conductive electrode and cathode shell. The obtained supercapacitor was named according to the biomass carbon sample and recorded as "raw".

[0057] Comparative Example 2

[0058] (1) Garlic peel biomass material was placed in a tubular resistance furnace; the temperature was raised to the desired carbonization temperature under a nitrogen atmosphere and kept for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 1 L / min; when the temperature of the tubular furnace dropped to 100°C, the nitrogen was stopped; and the carbonized sample was obtained after natural cooling to room temperature.

[0059] (2) The carbonized sample obtained in step (1) and potassium hydroxide are mixed and stirred in a mass ratio of 1:4 to obtain a solution; and the solution is placed in a forced air drying oven and dried at a temperature of 120°C.

[0060] (3) Add a small amount of deionized water to the dried sample obtained in step (2) and mix well, then place in a muffle furnace, heat to 350°C under a nitrogen atmosphere, keep warm for 2 hours, continue to heat to the experimental set temperature, keep warm for 2 hours, the heating rate is 5°C / min, the nitrogen flow rate is 1L / min, and an activated sample is obtained.

[0061] (4) Dissolving the activated sample obtained in step (3) in deionized water to obtain a turbid solution; heating the obtained turbid solution in a water bath and subjecting it to magnetic stirring, the water bath temperature is 80° C., the stirring time is 30 min, and then the sample is allowed to stand to precipitate, the supernatant is discarded, and this step is repeated until the pH value of the supernatant is 8, thereby obtaining a turbid solution.

[0062] (5) Add an appropriate amount of 1.0 M hydrochloric acid to the turbid liquid obtained in step (4) until the pH of the supernatant is 2, heat in a water bath and perform magnetic stirring at a water bath temperature of 80°C, continue stirring for 30 minutes, wash with deionized water after stirring until the supernatant is neutral, and then place in a forced air drying oven for 24 hours at a temperature of 105°C to obtain sample 2.

[0063] The prepared sample 2 was mixed evenly with conductive graphite and polytetrafluoroethylene solution (60wt%) at a mass ratio of 8:1:1 and a certain amount of anhydrous ethanol, and ultrasonically mixed for 30 minutes, and then coated on a nickel foam disc with a diameter of 1.5 cm. After vacuum drying at 80°C for 12 hours, the conductive electrode was obtained by pressing. The two electrodes, glass fiber diaphragm and battery shell were immersed in 6M KOH electrolyte, and the supercapacitor was assembled in the order of anode shell, conductive electrode, glass fiber diaphragm, conductive electrode and cathode shell. The obtained supercapacitor was named according to the biomass carbon sample, recorded as "KOH (1:4)".

[0064] Comparative Example 3

[0065] (1) Garlic peel biomass material was placed in a tubular resistance furnace; the temperature was raised to the desired carbonization temperature under a nitrogen atmosphere and kept for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 1 L / min; when the temperature of the tubular furnace dropped to 100°C, the nitrogen was stopped; and the carbonized sample was obtained after natural cooling to room temperature.

[0066] (2) The carbonized sample obtained in step (1) and potassium hydroxide are mixed and stirred in a mass ratio of 1:8 to obtain a solution; and the solution is placed in a forced air drying oven and dried at a temperature of 120°C.

[0067] (3) Add a small amount of deionized water to the dried sample obtained in step (2) and mix well, then place in a muffle furnace, heat to 350°C under a nitrogen atmosphere, keep warm for 2 hours, continue to heat to the experimental set temperature, keep warm for 2 hours, the heating rate is 5°C / min, the nitrogen flow rate is 1L / min, and an activated sample is obtained.

[0068] (4) Dissolving the activated sample obtained in step (3) in deionized water to obtain a turbid solution; heating the obtained turbid solution in a water bath and subjecting it to magnetic stirring, the water bath temperature is 80° C., the stirring time is 30 min, and then the sample is allowed to stand to precipitate, the supernatant is discarded, and this step is repeated until the pH value of the supernatant is 8, thereby obtaining a turbid solution.

[0069] (5) Add an appropriate amount of 1.0 M hydrochloric acid to the turbid liquid obtained in step (4) until the pH of the supernatant is 2, heat in a water bath and perform magnetic stirring at 80°C, continue stirring for 30 minutes, wash with deionized water after stirring until the supernatant is neutral, and then place in a forced air drying oven for 24 hours at 105°C to obtain sample 3.

[0070] The prepared sample 3 was mixed evenly with conductive graphite and polytetrafluoroethylene solution (60wt%) in a mass ratio of 8:1:1 and a certain amount of anhydrous ethanol, and after ultrasonic mixing for 30 minutes, it was coated on a nickel foam disc with a diameter of 1.5 cm, and vacuum dried at 80℃ for 12 hours, and then pressed to obtain a conductive electrode. The two electrodes, glass fiber diaphragm and battery shell were immersed in 6M KOH electrolyte, and the supercapacitor was assembled in the order of anode shell, conductive electrode, glass fiber diaphragm, conductive electrode and cathode shell. The obtained supercapacitor was named according to the biomass carbon sample, recorded as "KOH (1:8)".

[0071] Example 1

[0072] (1) Garlic peel biomass material was placed in a tubular resistance furnace; the temperature was raised to the desired carbonization temperature under a nitrogen atmosphere and kept for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 1 L / min; when the temperature of the tubular furnace dropped to 100°C, the nitrogen was stopped; and the carbonized sample was obtained after natural cooling to room temperature.

[0073] (2) The carbonized sample obtained in step (1) is mixed with potassium hydroxide in a mass ratio of 1:4, and stirred evenly with deionized water; the obtained slurry mixture is placed in a hydrodynamic cavitation treatment equipment, the rotation speed is 3500 rpm (revolutions / minute), the treatment time is 60 min, the diameter of the venturi hydrodynamic cavitation equipment is 15 mm, the throat diameter is 3 mm, and the contraction angle and expansion angle are 35°; the treated sample is placed in a blast drying oven and dried at a temperature of 120°C.

[0074] (3) Add a small amount of deionized water to the dried sample obtained in step (2), mix well and place in a muffle furnace, heat to 350°C under a nitrogen atmosphere, keep warm for 2 hours, continue to heat to the experimental set temperature, keep warm for 2 hours, the heating rate is 5°C / min, the nitrogen flow rate is 1L / min, and an activated sample is obtained.

[0075] (4) Dissolving the activated sample obtained in step (3) in deionized water to obtain a turbid solution; heating the obtained turbid solution in a water bath and subjecting it to magnetic stirring, the water bath temperature is 80° C., the stirring time is 30 min, and then the sample is allowed to stand to precipitate, the supernatant is discarded, and this step is repeated until the pH value of the supernatant is 8, thereby obtaining a turbid solution.

[0076] (5) Add an appropriate amount of 1.0 M hydrochloric acid to the turbid liquid obtained in step (4) until the pH of the supernatant is 2, heat in a water bath and perform magnetic stirring at 80°C, continue stirring for 30 min, wash with deionized water after stirring until the supernatant is neutral, and then place in a forced air drying oven for 24 h at 105°C to obtain sample 4.

[0077] The prepared sample 4 was mixed evenly with conductive graphite and polytetrafluoroethylene solution (60wt%) in a mass ratio of 8:1:1 and a certain amount of anhydrous ethanol, and ultrasonically mixed for 30 minutes, and then coated on a nickel foam disc with a diameter of 1.5 cm. After vacuum drying at 80°C for 12 hours, the conductive electrode was obtained by pressing. The two electrodes, glass fiber diaphragm and battery shell were immersed in 6M KOH electrolyte, and the supercapacitor was assembled in the order of anode shell, conductive electrode, glass fiber diaphragm, conductive electrode and cathode shell. The obtained supercapacitor was named according to the biomass carbon sample, recorded as "KOH (1:4) + HC".

[0078] Example 2

[0079] (1) Garlic peel biomass material was placed in a tubular resistance furnace; the temperature was raised to the desired carbonization temperature under a nitrogen atmosphere and kept for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 1 L / min; when the temperature of the tubular furnace dropped to 100°C, the nitrogen was stopped; and the carbonized sample was obtained after natural cooling to room temperature.

[0080] (2) The carbonized sample obtained in step (1) is mixed with potassium hydroxide in a mass ratio of 1:8, and deionized water is added to stir evenly; the obtained slurry mixture is placed in a hydrodynamic cavitation treatment equipment, the rotation speed is 3500 rpm (revolutions / minute) and the treatment time is 60 min. The diameter of the venturi hydrodynamic cavitation equipment is 15 mm, the throat diameter is 3 mm, and the contraction angle and expansion angle are 35°; the treated sample is placed in a blast drying oven and dried at a temperature of 120°C.

[0081] (3) Add a small amount of deionized water to the dried sample obtained in step (2), mix well and place in a muffle furnace, heat to 350°C under a nitrogen atmosphere, keep warm for 2 hours, continue to heat to the experimental set temperature, keep warm for 2 hours, the heating rate is 5°C / min, the nitrogen flow rate is 1L / min, and an activated sample is obtained.

[0082] (4) Dissolving the activated sample obtained in step (3) in deionized water to obtain a turbid solution; heating the obtained turbid solution in a water bath and subjecting it to magnetic stirring, the water bath temperature is 80° C., the stirring time is 30 min, and then the sample is allowed to stand to precipitate, the supernatant is discarded, and this step is repeated until the pH value of the supernatant is 8, thereby obtaining a turbid solution.

[0083] (5) Add an appropriate amount of 1.0 mol / L hydrochloric acid to the turbid liquid obtained in step (4) until the pH of the supernatant is 2, heat in a water bath and perform magnetic stirring at a water bath temperature of 80°C, continue stirring for 30 minutes, and after stirring, wash with deionized water until the supernatant is neutral, then place in a forced air drying oven and dry for 24 hours at a temperature of 105°C to obtain sample 5.

[0084] The prepared sample 5 was mixed evenly with conductive graphite and polytetrafluoroethylene solution (60wt%) at a mass ratio of 8:1:1 and a certain amount of anhydrous ethanol, and after ultrasonic mixing for 30 minutes, it was coated on a foam nickel disc with a diameter of 1.5 cm, and vacuum dried at 80℃ for 12 hours, and then pressed to obtain a conductive electrode. The two electrodes, glass fiber diaphragm and battery shell were immersed in 6M KOH electrolyte, and the supercapacitor was assembled in the order of anode shell, conductive electrode, glass fiber diaphragm, conductive electrode and cathode shell. The prepared supercapacitor was named according to the biomass carbon sample, recorded as "KOH (1:8) + HC".

[0085] The comparative examples and examples have a significant impact on the specific surface area and pore volume of garlic skin-based biochar: Figure 1 , Figure 2 The TEM images of KOH (1:4) and KOH (1:4) + HC respectively show that the ratio of micropores to mesopores increases significantly and the amount of impurities decreases after hydrodynamic cavitation treatment. This indicates that the micro-jet and local high temperature and high pressure environment generated by hydrodynamic cavitation not only physically promote the formation of micropores and mesopores, but also assist the diffusion of the activator, which is conducive to the chemical activation.

[0086] The specific surface areas of garlic peel-based biochar after activation with HC increased from 102 m 2 g -1 Increased to 1455m 2 g -1 and 2848m 2 g -1 .exist Figure 3 In the embodiment, it can be observed that after hydrodynamic cavitation synergistic activation at the same carbon-alkali ratio, the specific surface area of ​​KOH (1:4) + HC and KOH (1:8) + HC garlic skin-based biochar increased by 40.8% and 7.8% compared with KOH (1:4) and KOH (1:8), respectively. In addition, compared with single alkali activation, the total pore volume of KOH (1:4) + HC garlic skin-based biochar increased from 0.95 cm3 g -1 Increased to 1.22cm 3 g -1 , increased by 28.4%; the total pore volume of KOH (1:8) + HC garlic peel-based biochar increased from 2.01 cm 3 g -1 Increased to 2.7cm 3 g -1 , increased by 25.6%; and the micropore volume also showed the same trend, KOH (1:4)

[0087] Compared with KOH(1:4) and KOH(1:8)+HC, the 3 g -1 and 0.98cm 3 g -1 Increased to 0.88cm 3 g -1 and 1.07cm 3 g -1 , increased by 37.5% and 9.2% respectively. The specific capacitance of supercapacitors made of biomass carbon materials in KOH (1:8) + HC is as high as 173A g -1 , an improvement of 911.952% compared to the unprocessed samples. Figure 4 The XPS spectra of the samples prepared by KOH (1:4), KOH (1:4) + HC, KOH (1:8), and KOH (1:8) + HC show that there are four peaks in the C 1s spectrum: C = C (284.6 eV), CC (285.1 eV), C = O & C-N (286.1 eV), and O = CO (289.1 eV). The C = O & C-N bonds of the two samples treated with HC increase, and the nitrogen-containing functional groups and oxygen-containing functional groups can provide pseudocapacitance. The oxygen-containing functional groups increase, and C = O is a hydrophilic functional group, which can improve the hydrophilicity of the electrode material and increase the contact area between the electrode material and the electrolyte, which helps to improve the electrochemical performance of the obtained supercapacitor. The preparation process of the supercapacitor is as follows: the prepared sample is mixed evenly with conductive graphite and polytetrafluoroethylene solution (60wt%) at a mass ratio of 8:1:1 and a certain mass of anhydrous ethanol, and after ultrasonic mixing for 30 minutes, it is coated on a foam nickel disc with a diameter of 1.5 cm, and after vacuum drying at 80°C for 12 hours, the conductive electrode is obtained by pressing. The two electrodes, the glass fiber diaphragm and the battery shell are immersed in an electrolyte of 6M KOH, and the supercapacitor is assembled in the order of the anode shell, the conductive electrode, the glass fiber diaphragm, the conductive electrode and the cathode shell. Figure 5 To make KOH (1:4), KOH (1:4) + HC, KOH (1:

[0088] 8) KOH (1:8) + HC sample was used as electrode material and assembled into a symmetrical supercapacitor with 6M KOH as electrolyte at room temperature (25°C). -1 The curves obtained by the constant current charge and discharge test at a current density of , it can be observed that the supercapacitors prepared by the comparative example and the example samples are approximately triangular, with some deformation, which indicates that the material is mainly double-layer capacitor.

[0089] The charge and discharge time of the supercapacitor made of the KOH(1:8)+HC sample is nearly 100s, and the charge and discharge time of the supercapacitor made of the KOH(1:8)+HC sample is nearly 120s, which indicates that it has a higher specific capacitance. Figure 6 It shows that the samples prepared with KOH (1:4) + HC and KOH (1:8) + HC have no capacity decay after 5000 constant current charge and discharge cycles at 5A / g, and have good energy storage performance.

[0090] In the above characterization, the model of the specific surface area analyzer is: JW-BK132F, the model of the X-ray diffractometer is D / MAX-2500PC, the model of the Raman spectrometer is Renishaw inVia, and the model of the electrochemical workstation is CS350H.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing two-dimensional biomass carbon material by impregnation with an activator assisted by hydrodynamic cavitation, characterized in that: The steps include: Provide biomass carbonization samples; The biomass carbonized sample and the activator are added into water and mixed evenly, and then subjected to a hydrodynamic cavitation treatment, and then dried to obtain a dried sample; The dried sample is subjected to activation heat treatment to obtain an activated sample; The activated sample is purified.

2. The method for preparing two-dimensional biomass carbon material by impregnation activator assisted by hydrodynamic cavitation as claimed in claim 1, characterized in that: The mass ratio of biomass carbonization sample to activator is 1:2~10.

3. The method for preparing two-dimensional biomass carbon material by hydrodynamic cavitation assisted impregnation activator as claimed in claim 2, characterized in that: The mass ratio of biomass carbonization sample to activator is 1:7~9.

4. The method for preparing two-dimensional biomass carbon material by hydrodynamic cavitation assisted impregnation activator as claimed in claim 1, characterized in that: The activator is potassium hydroxide, sodium hydroxide or hydrochloric acid.

5. The method for preparing two-dimensional biomass carbon material by hydrodynamic cavitation assisted impregnation activator as claimed in claim 1, characterized in that: The hydraulic cavitation treatment adopts Venturi type hydraulic cavitation equipment.

6. The method for preparing two-dimensional biomass carbon material by impregnation activator assisted by hydrodynamic cavitation as claimed in claim 5, characterized in that: The hydrodynamic cavitation treatment conditions are as follows: the Venturi tube inlet pressure is 0.5~4 MPa, the treatment temperature is 30~70℃, and the treatment time is 10~120 min.

7. The method for preparing two-dimensional biomass carbon material by impregnation activator assisted by hydrodynamic cavitation as claimed in claim 1, characterized in that: The activation heat treatment is carried out under an inert atmosphere, and the process is: firstly heating to 50-400°C, keeping the temperature for 0.1-3 h, then continuing to heating to the set temperature of 600-900°C, keeping the temperature for 1-3 h.

8. The method for preparing two-dimensional biomass carbon material by impregnation activator assisted by hydrodynamic cavitation as claimed in claim 1, characterized in that: The biomass carbonization samples were obtained by pyrolysis and carbonization of biomass.

9. The method for preparing two-dimensional biomass carbon material by impregnation activator assisted by hydrodynamic cavitation as claimed in claim 8, characterized in that: The heating rate of pyrolysis carbonization is 1-10 ℃ / min, and the holding time is 1-2 h.

10. The method for preparing two-dimensional biomass carbon material by impregnation activator assisted by hydrodynamic cavitation as claimed in claim 1, characterized in that: The purification treatment includes water washing and acid treatment.

11. The method for preparing two-dimensional biomass carbon material by impregnation activator assisted by hydrodynamic cavitation as claimed in claim 1, characterized in that: The preparation process is as follows: (1) Place the garlic peel biomass material in a tubular resistance furnace; carbonize it in a nitrogen atmosphere, and obtain a carbonized sample after naturally cooling to room temperature; (2) mixing the carbonized sample obtained in step (1) with potassium hydroxide in a certain mass ratio, adding deionized water and stirring evenly; placing the obtained slurry mixture in a hydraulic cavitation treatment device for hydraulic cavitation treatment, and placing the treated sample in a blast drying oven for drying; (3) adding a small amount of deionized water to the dried sample obtained in step (2), mixing evenly, and placing the mixture in a muffle furnace for activation to obtain an activated sample; (4) dissolving the activated sample obtained in step (3) in deionized water to obtain a turbid solution; heating the obtained turbid solution in a water bath and subjecting it to magnetic stirring, and then allowing the sample to settle, discarding the supernatant, and repeating this step until the supernatant is neutral to obtain a turbid solution; (5) Add an appropriate amount of hydrochloric acid to the turbid liquid obtained in step (4), heat it in a water bath and stir it magnetically, then let the turbid liquid stand, wash the precipitate with deionized water until it is neutral, and then dry it in a forced air drying oven to obtain activated carbon.

12. A two-dimensional biomass carbon material, characterized in that: The method is prepared by any one of claims 1 to 11.

13. Use of the two-dimensional biomass carbon material according to claim 12 as an electrode material in a supercapacitor.

Citation Information

Patent Citations

  • Method for promoting biomass hydrolysis and preparing reducing sugar through supercritical carbon dioxide and ultrasonic coupled pretreatment

    CN102586493A

  • Preparation method for biomass base active carbon electrode material

    CN107665777A